Me-search and re-search : a guide for writing scholarly personal narrative manuscripts - Nash, Robert J.; Bradley, DeMethra LaSha (Emerald Publishing Limited : Information Age Publishing, 2011)
What we intend to do in this book is to explain, and exemplify, in a nuts-and-bolts way, what we are calling Scholarly Personal Narrative (SPN) writing. This is a genre created over 15 years ago by Robert, one of the co-authors of this book. The other co-author, DeMethra, has actually written a thesis and dissertation using this genre, so she brings an author's direct SPN experience to the table. Both of us co-teach a course that we call "Scholarly Personal Narrative Writing for Pre-Professionals and Professionals." In the chapters that follow, we will present a step-by-step approach for composing an SPN manuscript. The book will be comprised of four general parts, consisting of several short, practical chapters, written in non-technical language. We will write each of the chapters as a way of responding to the most common questions that our students have raised about SPN writing through the years. We will attempt to write as we teach, with no frills and with clarity, empathy, and understanding. We will also provide several SPN writing examples, as well as authorial toolbox tips, throughout the book. In addition, we will conclude with a bibliography of the most relevant personal narrative writing guides we have been able to muster. Our desire is to minimize the number of in-text citations and references in order to maximize the space for us to present a useful, nuts-and-bolts guide to writing, as well as a realistic, down-to-earth rationale for scholarly personal narrative writing in the academy. After reading the book, and practicing the writing exercises, undergraduate and graduate students will be able to author research papers, theses, and dissertations using the Scholarly Personal Narrative research genre. Hundreds of students have done this already throughout the country.
Keywords: Authorship.; Academic writing.; Report writing -- Study and teaching.; Critical thinking -- Study and teaching.; Education -- Research.; Education.; elektronické knihy; electronic books